The Test For Lead (Pb) Iron (Fe) And Content Zink (Zn) In The Water Of The Bah Bolon River Pematangsiantar City - Sirait, Anjona; Sinaga, Mardame Pangihutan; Siburian, Daniel Tony E. (Jurnal Ilmiah Platax, 2024)
This research aims to determine the levels of heavy metals lead (Pb), iron (Fe), and zinc (Zn) in the Bah Bolon River water, Pematangsiantar City. This research was conducted in August-September 2023. Water samples were collected by selecting 3 research stations with 3 repetitions. Then the heavy metal content of the samples was analyzed using the Atomic Absorption Spectrophotometry (SSA) method. The results of this study show that the levels of the heavy metal iron (Fe) are higher than the heavy metals (Pb) and (Zn). The test results for iron (Fe) at all stations ranged from 0.08-0.51 mg/L, lead (Pb ) of 0.003 mg/L, zinc (Zn) ranges from 0.001 mg/L, temperature ranges from 25.06-26.9 oC, pH ranges from 7.18-7.61, DO ranges from 6.33-7.2 mg/L The quality of Bah Bolon river waters based on PPRI No.22 of 2021 for the parameters of lead (Pb), zinc (Zn), iron (stations 2 and 3), pH, DO, and temperature still meets class 2 quality standards and is suitable for use. used as a source of irrigation or agricultural water and the iron (Fe) content at station 1 has exceeded the quality standard limit and is no longer suitable for use. Keywords: Iron, heavy metals, lead, and zinc Abstrak Penelitian ini bertujuan untuk mengetahui kadar logam berat timbal (Pb), besi (Fe), dan zink (Zn) di dalam air sungai Bah Bolon Kota Pematangsiantar. Penelitian ini dilakukan pada bulan Agustus-September 2023. Pengambilan sampel air dilakukan dengan memilih 3 stasiun penelitian dengan 3 kali pengulangan. Kemudian kandungan logam berat sampel dianalisis menggunakan metode Spektrofotometri Serapan Atom (SSA). Hasil penelitian ini menunjukkan bahwa kadar logam berat besi (Fe) lebih tinggi dibandingkan logam berat (Pb) dan ((Zn). Hasil uji  besi (Fe) pada semua stasiun berkisar 0,08-0,51 mg/L, timbal (Pb) sebesar 0,003 mg/L, zink (Zn) berkisar 0,001 mg/L, suhu berkisar 25,06-26,9 oC, pH berkisar 7,18-7,61, DO berkisar 6,33-7,2 mg/L. Kualitas perairan sungai Bah Bolon berdasarkan PPRI No.22 Tahun 2021 untuk parameter timbal (Pb), zink (Zn), besi (stasiun 2 dan 3), pH, DO, dan suhu,  masih memenuhi standar baku mutu kelas 2 dan layak untuk digunakan sebagai sumber air irigasi atau pertanian dan untuk kandungan besi (Fe) di Stasiun 1 telah melebihi batas baku mutu dan tidak layak untuk digunakan lagi. Kata kunci: Besi, Logam berat, Timbal dan zink